Transport and geographical position of medium-sized cities in the western regions of Ukraine - Oksana Yatsko (Časopis Socìalʹno-Ekonomìčnoï Geografìï. Часопис соціально-економічної географії, 2016)
Due to the compactness and high concentration of socio-economic phenomena urban areas require a developed transport infrastructure and a coherence in communication with the surrounding territory and centres of different levels to ensure the proper functioning. The article is dedicated to estimation of the position of medium-sized cities in an Western part ofUkrainerelative to the existing transport system. Particular attention is paid to location relative to international transport corridors and European routes, to the proximity and transport accessibility to state border checkpoints.